Renal sympathetic nerve activation via α2-adrenergic receptors in chronic kidney disease progression - Hee-Seong Jang; Jinu Kim; Babu J. Padanilam (The Korean Society of Nephrology, 2019)
Chronic kidney disease (CKD) is increasing worldwide without an effective therapeutic strategy. Sympathetic nerve activation is implicated in CKD progression, as well as cardiovascular dysfunction. Renal denervation is beneficial for controlling blood pressure (BP) and improving renal function through reduction of sympathetic nerve activity in patients with resistant hypertension and CKD. Sympathetic neurotransmitter norepinephrine (NE) via adrenergic receptor (AR) signaling has been implicated in tissue homeostasis and various disease progressions, including CKD. Increased plasma NE level is a predictor of survival and the incidence of cardiovascular events in patients with end-stage renal disease, as well as future renal injury in subjects with normal BP and renal function. Our recent data demonstrate that NE derived from renal nerves causes renal inflammation and fibrosis progression through alpha-2 adrenergic receptors (α2-AR) in renal fibrosis models independent of BP. Sympathetic nerve activation-associated molecular mechanisms and signals seem to be critical for the development and progression of CKD, but the exact role of sympathetic nerve activation in CKD progression remains undefined. This review explores the current knowledge of NE-α2-AR signaling in renal diseases and offers prospective views on developing therapeutic strategies targeting NE-AR signaling in CKD progression.